1998
DOI: 10.1007/s005850050587
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric conductance distribution and MHD wave structure: observation and model

Abstract: Abstract. The ionosphere in¯uences magnetohydrodynamic waves in the magnetosphere by damping because of Joule heating and by varying the wave structure itself. There are di erent eigenvalues and eigensolutions of the three dimensional toroidal wave equation if the height integrated Pedersen conductivity exceeds a critical value, namely the wave conductance of the magnetosphere. As a result a jump in frequency can be observed in ULF pulsation records. This e ect mainly occurs in regions with gradients in the Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 15 publications
(17 reference statements)
1
22
0
Order By: Relevance
“…Although Budnik et al [1998] did not solve for the fieldaligned eigenmodes, they inferred that when the Pedersen conductivity at one end of the field line became less than a critical conductivity given by S P critical = 1/m 0 A I where A I is the Alfvén speed at the ionosphere (S P critical = 0.35 S for their case) the mode would change from a half-to a quarterwavelength harmonic. They observed a sharp frequency change from 18 -19 mHz to 5 -6 mHz, which could be consistent with this mode change.…”
Section: A05205mentioning
confidence: 99%
See 1 more Smart Citation
“…Although Budnik et al [1998] did not solve for the fieldaligned eigenmodes, they inferred that when the Pedersen conductivity at one end of the field line became less than a critical conductivity given by S P critical = 1/m 0 A I where A I is the Alfvén speed at the ionosphere (S P critical = 0.35 S for their case) the mode would change from a half-to a quarterwavelength harmonic. They observed a sharp frequency change from 18 -19 mHz to 5 -6 mHz, which could be consistent with this mode change.…”
Section: A05205mentioning
confidence: 99%
“…(Note that Figure 11 shows the effect of changing S P N from symmetric conductivities of 5 S to 0.1 S). In addition, Figure 11 also illustrates how the wave damping rate, w 0 /g, depends on S P N with maximum wave damping occurring when S P N ' 1 S. [29] Budnik et al [1998] presented a satellite observation at L = 6.8 of a pulsation event with a sharp frequency change observed both in the radial and azimuthal magnetic Figure 10. The magnetic perturbations of guided poloidal fundamental quarter-wavelength modes at L = 4 calculated using an equatorial plasma density of 567 amu/cm 3 and a field-aligned plasma density profile /1/r 3 .…”
Section: A05205mentioning
confidence: 99%
“…The D component showed strongly asymmetric amplitude with 90°phase difference between conjugate points when one hemisphere was sunlit and the other was dark. Budnik et al (1998) reported a pulsation event of 18-19 mHz, recorded by the GOES-6 satellite. It was seen that as the satellite was crossing the dusk terminator, the frequency abruptly decreased to 5-6 mHz.…”
Section: Introductionmentioning
confidence: 99%
“…It is often assumed that the ionospheric signatures of magnetospheric processes are very similar at conjugate points in the Northern and Southern Hemispheres. However, differences between the two hemispheres can occur due to the tilt of the Earth's rotational and magnetic axes, the offset of the magnetic dipole, the orientation of the interplanetary magnetic field (e.g., Østgaard et al, 2011a, 2011b; Tenfjord et al, 2015, 2017), and the asymmetry between the northern and southern ionospheres due to seasonal differences in solar illumination (e.g., Budnik et al, 1998). While all of these effects are important, this study will focus on the seasonal differences in the conjugate ionospheres.…”
Section: Introductionmentioning
confidence: 99%